Analysis of the Antibiotic Resistance Problem in the Agricultural Sector - E. N. Olsufyeva; V. S. Yankovskaya (Антибиотики и Химиотерапия, 2025)
Antimicrobial resistance is a major global threat to public health and development. The problem of antibiotic resistance arose as a result of widespread and uncontrolled use of antimicrobial drugs in medicine and agriculture. Antimicrobials, including antibiotics, are widely used in modern agriculture to treat animals, birds, and other domestic animals, as well as in the food industry. A decrease in the sensitivity of bacteria to certain classes of antibiotics was discovered as early as the very beginning of the antibiotic discovery era, which subsequently, in some cases, transformed into multidrug resistance. The resistance of microorganisms depends on the structure of the antibiotic and is associated with the mechanism of its antibacterial activity. The review examines the properties of various groups of antibiotics that are critically important in terms of the resistance problem, intended for the treatment, prevention, and growth stimulation of farm animals. The possibilities of using methods alternative to antibiotic therapy in veterinary medicine were also discussed.